(untitled) (Sotang, Yearly Peer Reviewed Journal, 2024)
Various social, economic, and academic factors significantly contribute to students’ dropout rates at the bachelor’s level, affecting their educational attainment and posing challenges to higher education systems. This collaborative mini-research aimed to investigate the status of students’ dropout rate in bachelor’s level at Solukhumbu Multiple Campus and to explore the influencing factors for students’ dropout. The researchers employed a mixed-method approach with a survey design, utilizing a pre-formulated questionnaire containing both open and closed-ended questions. Data were collected from primary and secondary sources. The sample consisted of 56 dropout students from Solukhumbu Multiple Campus, selected using census sampling from three faculties (B.Ed., BBS, and B.A.) across admission year 2075 and exam years 2076-2079. This study identifies pronounced gender-based disparities in factors influencing student dropout rates. Female respondents expressed significantly higher dissatisfaction with the examination system, citing marriage and child rearing as major impediments to academic progress. They were more likely to attribute low examination performance and inadequate family support to their dropout decisions, emphasizing the critical roles of timely exam scheduling and parental awareness. In contrast, males were less concerned with these issues, instead highlighting employment opportunities and entrepreneurial ventures as pivotal factors in their decision to discontinue studies. These findings highlight the importance of implementing gender-sensitive strategies to improve student retention.